Validation of training levels in endoscopic endonasal surgery of the skull base. (7th March 2019) - Lavigne, Philippe; Faden, Daniel; Gardner, Paul A.; Fernandez‐Miranda, Juan C.; Wang, Eric W.; Snyderman, Carl H.
Abstract : Objective: A five‐level training program was first proposed 10 years ago for surgeons learning endoscopic endonasal surgery (EES) of the skull base. Levels were based on the complexity of anatomy, risk of neurovascular injury, intradural dissection, technical difficulty and vascularity of tumors. Method: A three‐phase validation concept is proposed: 1) face validity (the classification is related to clinically significant elements), 2) construct validity (the classification predicts the outcome), and 3) inter‐team validation (the classification applies to other surgical teams). Consecutive cases over a 1‐year time span were retrospectively classified. Primary outcome measures included: complication rates (cranial nerve injury, stroke and vascular injury, cerebrospinal fluid [CSF] leak and infection), estimated blood loss and duration of surgery. Results: Two hundred and nine consecutive cases were analyzed. The distribution of cases for each category was: 63 cases in level II, 70 cases in level III, 66 cases in level IV, and 10 cases in level V. Construct validity demonstrated statistical difference with increasing rate of complications from level II to level III and from level III to level IV; also, specific rates of cranial nerve injury and CSF leak increased between levels III and IV. Face validity identified 162 citations since publication of the original article. Inter‐team validation demonstrated no difference between two teams of surgeons. Conclusion: This study provides a three‐phase validation of training levels for endoscopic skull base surgery. Adoption of a progressive systematic approach to learning EES from least complex to advanced procedures is expected to minimize the risks while surgical teams gain experience. Level of Evidence: 3 Laryngoscope, 129:2253–2257, 2019